Extending the human connectome project across ages: imaging protocols for the lifespan development and aging projects - Harms, MP; Somerville, LH; Ances, BM; Andersson, J; Barch, DM; Bastiani, M; Bookheimer, SY; Brown, TB; Buckner, RL; Burgess, GC; Coalson, TS; Chappell, MA; et al. (Elsevier, 2018)
The Human Connectome Projects in Development (HCP-D) and Aging (HCP-A) are two large-scale brain imaging studies that will extend the recently completed HCP Young-Adult (HCP-YA) project to nearly the full lifespan, collecting structural, resting-state fMRI, task-fMRI, diffusion, and perfusion MRI in participants from 5 to 100 + years of age. HCP-D is enrolling 1300 + healthy children, adolescents, and young adults (ages 5-21), and HCP-A is enrolling 1200 + healthy adults (ages 36-100+), with each study collecting longitudinal data in a subset of individuals at particular age ranges. The imaging protocols of the HCP-D and HCP-A studies are very similar, differing primarily in the selection of different task-fMRI paradigms. We strove to harmonize the imaging protocol to the greatest extent feasible with the completed HCP-YA (1200 + participants, aged 22-35), but some imaging-related changes were motivated or necessitated by hardware changes, the need to reduce the total amount of scanning per participant, and/or the additional challenges of working with young and elderly populations. Here, we provide an overview of the common HCP-D/A imaging protocol including data and rationales for protocol decisions and changes relative to HCP-YA. The result will be a large, rich, multi-modal, and freely available set of consistently acquired data for use by the scientific community to investigate and define normative developmental and aging related changes in the healthy human brain.